2011
DOI: 10.1371/journal.pone.0021727
|View full text |Cite
|
Sign up to set email alerts
|

Optimised Motion Tracking for Positron Emission Tomography Studies of Brain Function in Awake Rats

Abstract: Positron emission tomography (PET) is a non-invasive molecular imaging technique using positron-emitting radioisotopes to study functional processes within the body. High resolution PET scanners designed for imaging rodents and non-human primates are now commonplace in preclinical research. Brain imaging in this context, with motion compensation, can potentially enhance the usefulness of PET by avoiding confounds due to anaesthetic drugs and enabling freely moving animals to be imaged during normal and evoked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 29 publications
2
55
0
1
Order By: Relevance
“…It is nevertheless clear that with appropriate environmental control, 18 F-FDG imaging can be exploited in cognitively active animals for both tumor imaging (32) and the detection of metabolism in performance-related brain centers (38)(39)(40), strongly supporting the notion that behavioral control after 18 F-FDG administration may indeed increase the homogeneity of absolute radioactivity in the brain.…”
Section: Discussionmentioning
confidence: 95%
“…It is nevertheless clear that with appropriate environmental control, 18 F-FDG imaging can be exploited in cognitively active animals for both tumor imaging (32) and the detection of metabolism in performance-related brain centers (38)(39)(40), strongly supporting the notion that behavioral control after 18 F-FDG administration may indeed increase the homogeneity of absolute radioactivity in the brain.…”
Section: Discussionmentioning
confidence: 95%
“…In Emmi et al [20] and Crescimanno et al [21], rats with specific brain lesions were found to execute single-axis head turns with a maximum speed of 130 deg s 21 . The study of Jobbagy et al [22] reported head location and direction measurements of rats housed in inclined tubes, but the temporal resolution of the measurements (250 ms) was not suitable for assessing instantaneous speed [23].…”
Section: Rodent Head Motionmentioning
confidence: 99%
“…I N PET brain imaging, rigid motion correction can be obtained based on pose measurement using optical motion tracking [1], [2]. Previously we have applied a similar rigid motion correction technique to helical CT brain scans, by measuring the head motion with a Polaris system (Spectra, Northern Digital Inc., Waterloo, Canada) [3], [4].…”
Section: Introductionmentioning
confidence: 99%